Analisis Evaluatif Buku Teks Bahasa Arab Siswa Kelas 4 Madrasah Ibtidaiyah Terbitan Kementerian Agama Tahun 2020 - Anjarwati Anjarwati; Dian Risky Amalia; Kholida Nur (JICALLS: Journal of Arabic Education, Linguistics, and Literature Studies, 2024)
Textbooks are an effective learning alternative to improve students' understanding of material. The research aims to analyze the Arabic language textbook for fourth grade Madrasah Ibtidaiyah, published by the Ministry of Religion, as an effective learning tool. The method used in this research is a qualitative method and literature study, utilizing primary data sources from the grade 4 Arabic textbooks published by the Ministry of Religion, as well as relevant secondary data sources from appropriate journals. The research also employs the content analysis method to assess the 2020 edition of the fourth grade Arabic textbook. The findings indicate that the teaching material largely meets the quality standards set by the KMA, with good physical quality, well-structured content, relevant illustrations, varied exercises, and appropriate references.